Effects of Soil Modulus and Flexural Rigidity on Structural Analysis of Water Intake Basins - Hassan Akbari (Civil Engineering Journal, 2017)
A water intake basin is a buried box that functions as a water reservoir near shorelines. Number of these structures has been increased in the recent years and for a safe design, it is necessary to know their behaviour under applied loads. In addition to common dead, live and seismic loads, the bottom of such a basin is usually located below sea water level and endures uplift pressure as well as reaction of supporting soils. Uncertainty of these special loads complicates the structural response of this buried basin to the applied loads. Therefore, the unreliability in the soil parameter and in the rigidity of the basin structure is studied in this research by calculating the generated internal bending moments. Different loads and load combinations have been taken into account and finite element analysis is carried out for modelling nonlinear behaviour of different types of supporting soils. It is concluded that the geometry and flexural stiffness of the basin affects the analysis more than the soil parameters because the contribution of the soil modulus in the total stiffness of the system is negligible than the structural rigidity of the basin structure. In addition, inner walls and geometry of the basin should be modelled in detail to obtain acceptable results.